Effects of Exenatide and Humalog Mix25 on Fat Distribution, Insulin Sensitivity, and β-Cell Function in Normal BMI Patients with Type 2 Diabetes and Visceral Adiposity. (27th May 2020) - Wang, Xinlei; Zhao, Xiaoqin; Gu, Yunjuan; Zhu, Xiaohui; Yin, Tong; Tang, Zhuqi; Yuan, Jin; Chen, Wei; OuYang, Rong; Yao, Lili; Zhang, Rongping; Yuan, Jie; et al.
Abstract : In China, most normal BMI (body mass index of ≥18.5 to <25 kg/m 2 ) adults with type 2 diabetes (T2DM) exhibit visceral adiposity. This study compared the effects of exenatide and humalog Mix25 on normal BMI patients with T2DM and visceral adiposity. A total of 95 patients were randomized to receive either exenatide or humalog Mix25 treatment for 24 weeks. Subcutaneous adipose tissue (SAT) and visceral adipose tissue (VAT) were quantified by magnetic resonance imaging (MRI) and liver fat content (LFC) by liver proton magnetic resonance spectroscopy ( 1 H MRS). Each patient's weight, waist circumference, BMI, blood glucose, insulin sensitivity, pancreatic β -cell function, and fibroblast growth factor 21 (FGF-21) levels were measured. Data from 81 patients who completed the study (40 and 41 in the exenatide and humalog Mix25 groups, respectively) were analysed. The change in 2 h plasma blood glucose was greater in the exenatide group (P = 0.039 ). HOMA-IR and MBCI improved significantly after exenatide therapy (P < 0.01, P = 0.045 ). VAT and LFC decreased in both groups (P < 0.01 for all) but to a greater extent in the exenatide group, while SAT only decreased with exenatide therapy (P < 0.01 ). FGF-21 levels declined more in the exenatide group (P < 0.01 ), but were positively correlated with VAT in the entire cohort before (r = 0.244, P = 0.043 ) and after (r = 0.290, P = 0.016 ) the intervention. The effects of exenatide on glycaemic metabolism, insulin resistance, pancreatic β -cell function, and fat deposition support its administration to normal BMI patients with T2DM and visceral adiposity.